Haploinsufficiency of SF3B2 causes craniofacial microsomia - Andrew T. Timberlake (Nature Portfolio, 2021)
Despite being a common congenital facial anomaly, the genetic etiology of craniofacial microsomia (CFM) is not well understood. Here, the authors use exome and genome sequencing of 146 individuals with CFM to identify haploinsufficient variants in SF3B2 as a prevalent underlying cause.